Preparation and degradation method of degradable resin-based composite material
By introducing porous materials of metal salts and strong alkalis into resin-based composite materials, combined with high-frequency magnetic field technology, the efficient degradation of resin-based composite materials and the high-value reuse of full components are achieved, solving the problems of low degradation efficiency and expensive equipment in the prior art.
Patent Information
- Application Number
- CN202510462699.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2025-07-08
AI Technical Summary
The degradation efficiency of existing resin-based composite materials is low. Only the single component of fiber or resin is recovered, and the high-value reuse of the entire component cannot be achieved. The degradation process is cumbersome and the equipment is expensive.
The aqueous solution of metal salt and strong alkali is adsorbed in the porous material, and then blended with the degradation solvent after drying to form a porous material. The reaction of the metal salt and the solvent is triggered through a high-frequency magnetic field to achieve accurate degradation, the degradation efficiency is improved by using porous carriers and magnetic materials, and the material stability is maintained through the polymer nanoseal film.
Controllable and efficient degradation is achieved, the high-value reuse rate of the full component of resin-based composite materials is improved, the degradation process is simplified, and the equipment cost is reduced.
Smart Images

Figure CN120271962A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of materials, and relates to a preparation and degradation method of a resin-based composite material. Background Art
[0002] Continuous fiber-reinforced resin-based composite materials are widely used in industrial fields such as aerospace, automotive, and shipbuilding due to their low density and excellent mechanical properties. Traditional manufacturing processes are costly due to mold limitations and cannot form complex components.
[0003] Resin-based composite materials, especially epoxy resins and their composites, are widely used in multiple fields. For example, epoxy thermosetting materials are used in electrical engineering for gas-insulated enclosed switches and dry-type transformers, while in the aerospace, automotive, and wind power industries, fiber-reinforced epoxy composites are favored for their light weight, high durability, and good load-bearing capacity. These materials are usually embedded with glass or carbon fibers to form high-performance composite materials. However, the degradation and recycling of these materials face huge challenges. Traditional degradation methods require harsh chemical conditions, complex chemical syntheses, and expensive catalysts, which not only increase economic costs but also make it difficult to effectively solve the recycling problem of a large amount of existing waste. In addition, the negative environmental impact of plastic waste is becoming increasingly significant, making it particularly urgent to promote the development of a circular plastic economy.
[0004] Although composite materials can be recycled through pyrolysis, mechanical, and chemical recycling methods, there are still problems such as low degradation efficiency, only recovering single components of fibers or resins, being unable to achieve high-value reuse of all components of the composite material, and having a cumbersome degradation process and expensive degradation equipment. Summary of the Invention
[0005] In order to solve the problems of low degradation efficiency, only recovering single components of fibers or resins, being unable to achieve high-value reuse of all components of the composite material, having a cumbersome degradation process, and expensive degradation equipment, the present invention provides a preparation and degradation method of a degradable resin-based composite material, thereby improving the degradation efficiency and achieving the recovery of high-value products.
[0006] The object of the present invention is achieved by the following technical solutions:
[0007] A preparation method of a degradable resin-based composite material, comprising the following steps:
[0008] Step 1: Adsorb an aqueous solution of a metal salt and a strong base on a porous material, dry, and remove moisture to obtain a porous material 1 with a metal salt and a strong base adsorbed on its surface, wherein:
[0009] The metal salt is one or more of nitrates, sulfates, chlorides, phosphates, and acetates;
[0010] The nitrate is one or more of sodium nitrate, potassium nitrate, ammonium nitrate, calcium nitrate, lead nitrate, and cerium nitrate;
[0011] The sulfate is one or more of ferric sulfate, copper sulfate, sodium sulfate, potassium sulfate, potassium alum, sodium sulfate, magnesium sulfate, and aluminum sulfate;
[0012] The chloride is one or more of sodium chloride, potassium chloride, calcium chloride, magnesium chloride, zinc chloride, ferrous chloride, ferric chloride, copper chloride, silver chloride, barium chloride, ammonium chloride, and aluminum chloride;
[0013] The phosphate is one or more of ferric phosphate, copper phosphate, sodium phosphate, potassium phosphate, and magnesium phosphate;
[0014] The acetate is one or more of ferric acetate, copper acetate, sodium acetate, potassium acetate, and magnesium acetate;
[0015] The metal salt is preferably one or two of sodium sulfate, potassium sulfate, and potassium chloride;
[0016] The strong base is one or more of triethylamine, hexamethylenetetramine, ethylenediamine, propylenediamine, butylenediamine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, pyridine, imidazole, piperidine, sodium amide, sodium sulfide, sodium fluoride, potassium fluoride, ammonia water, sodium hydroxide, potassium hydroxide, calcium hydroxide, barium hydroxide, sodium methoxide, sodium ethoxide, n-butyllithium, and methyllithium;
[0017] The mass ratio of the metal salt to the strong base is 10:90 to 10, preferably 10:90 to 60;
[0018] In the aqueous solution of the metal salt and the strong base, the mass fractions of the metal salt and the strong base are both 0.5 to 30%, preferably 10 to 30%;
[0019] The porous material is one or more of porous ceramics, porous metals, porous polymers, carbon-based porous materials, metal-organic frameworks (MOFs), zeolites, molecular sieves, montmorillonite, etc.;
[0020] The porous ceramic is one or more of alumina porous ceramics, silicon carbide porous ceramics, zeolite molecular sieves, diatomite ceramics, zirconia porous ceramics, and mullite porous ceramics;
[0021] The pore size distribution of the porous material is 2 to 10 nm, preferably 5 to 8 nm.
[0022] The drying temperature is 60 to 120 °C, preferably 80 to 100 °C, and the drying time is 0.5 to 24 h, preferably 1 to 6 h;
[0023] Step 2: Immerse the porous material 1 in the degradation solvent. After adsorption saturation, the porous material 2 adsorbed with metal salts and the degradation solvent is obtained, where:
[0024] The degradation solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, benzyl alcohol, phenethyl alcohol, n-hexanol, 1,3-propanediol, glycerol, fructose, pentaerythritol, 1,2-propanediol (1,2-PG), 1,4-butanediol (BDO), 1,6-hexanediol (HD), neopentyl glycol, ethylene glycol, tetramethylbenzyl alcohol, ethyl acetate, isopropanol, phenethyl alcohol;
[0025] Step 3: Blend the porous material 2 with the magnetic material, form an aqueous dispersion through ultrasonic treatment and centrifugal purification, then wrap it in the polymer solution to form a polymer nano-sealing film on the surface, filter and dry to obtain the porous material 3, where:
[0026] The magnetic material is one or two of ferromagnetic materials and ferrimagnetic materials;
[0027] The ferromagnetic material is one or more of iron, nickel, cobalt, permalloy, magnetite (Fe3O3), neodymium iron boron (Nd2Fe 14 B, permanent magnet), samarium cobalt (SmCo5, permanent magnet), alnico (AlNiCo, permanent magnetic alloy);
[0028] The particle size distribution of the magnetic material is 2 - 10 nm, preferably 4 - 8 nm;
[0029] The mass ratio of the porous material 2 to the magnetic material is 100:2 - 60, preferably 100:20 - 50;
[0030] The polymer solution is one or more of polyvinylidene fluoride (PVDF) solution, polymethyl methacrylate (PMMA) solution, polyethylene (PE) solution, polytetrafluoroethylene (PTFE) solution, polyvinyl chloride (PVC) solution, polystyrene (PS) solution, polyacrylate (PAA) solution, polypropylene (PP) solution;
[0031] The mass fraction of the aqueous dispersion is 0.1 - 30%, preferably 3 - 12%;
[0032] The intensity of the ultrasonic treatment is 0.1 - 0.5 W / cm 2 preferably 0.2 - 0.4 W / cm 2 more preferably 0.2 - 0.3 W / cm 2 The time of the ultrasonic treatment is 0.1 - 24 h, preferably 1 - 4 h, more preferably 1 - 2 h;
[0033] The intensity of centrifugation is 100 to 10,000 rad / min, preferably 1,500 to 6,000 rad / min, more preferably 5,000 to 6,000 rad / min, and the time of centrifugation is 0.1 to 15 min, preferably 5 to 10 min, more preferably 8 to 10 min;
[0034] The temperature of drying is 60 to 150 °C, preferably 80 to 120 °C, and the time of drying is 0.1 to 2 h, preferably 1 to 2 h;
[0035] Step 4: Melting and blending the porous material 3 with the polymer matrix to obtain a degradable resin, and further curing to obtain a degradable composite material, wherein:
[0036] The polymer matrix is one or more of phenolic resin, epoxy resin, unsaturated polyester resin, polyurethane resin, melamine formaldehyde resin, polyether ether ketone, polyphenylene sulfide, polysulfone, acrylonitrile-butadiene-styrene copolymer, polymethyl methacrylate, thermoplastic polyurethane, polyamide, polycarbonate, polyoxymethylene, polyethylene terephthalate, polybutylene terephthalate, etc., preferably one or more of epoxy resin, unsaturated polyester resin, etc.;
[0037] The mass ratio of the porous material 3 to the polymer matrix is 10 to 30:100, preferably 10 to 15:100.
[0038] The temperature of melting is 5 to 300 °C, preferably 160 to 240 °C, the time of melting is 0.1 to 6 h, preferably 1 to 3 h, and the gradient heating rate is 10 to 60 °C / h, preferably 30 to 60 °C / h.
[0039] The temperature of curing is 20 to 200 °C, preferably 80 to 150 °C, the pressure is 0.1 to 20 Mpa, preferably 0.5 to 5 Mpa, and the curing time is 0.1 to 6 h, preferably 2 to 4 h.
[0040] A method for degrading a resin-based composite material prepared by the above method, comprising the following steps:
[0041] Using a high-frequency magnetic field to act on the degradable composite material to generate local high temperature, and the metal salt and the degradation solvent generate high pressure and highly active free radicals at high temperature, and the composite material can be degraded in a short time, wherein:
[0042] The frequency range of the high-frequency magnetic field is 20 to 300 MHz, preferably 200 to 300 MHz, the intensity of the magnetic field is 0.1 to 10 μT, preferably 1 to 8 μT, and the electric field intensity is 1 to 200 V / m, preferably 120 to 200 V / m.
[0043] Compared with the prior art, the present invention has the following advantages:
[0044] (1) Controllable degradation: The high-frequency magnetic field is used to trigger the reaction between metal salts and solvents to achieve precise degradation.
[0045] (2) Porous carrier optimization: zeolites, MOFs, etc. improve the loading efficiency of metal salts / solvents.
[0046] (3) Magnetic heat source: Fe3O4, Nd2Fe 14 B etc. to enhance high frequency magnetic field responsiveness.
[0047] (4) Polymer sealing: PVDF, PMMA and other membrane layers prevent premature degradation and ensure stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is the degradation product diagram of resin-based composite materials;
[0049] Figure 2 is the SEM image of the fiber after degradation;
[0050] Figure 3 is the stress-strain curve of a single glass fiber after degradation by degradation liquid;
[0051] Figure 4 This is the Fourier transform infrared spectrum of the resin product after degradation by the degradation liquid. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0053] The reagents used in the examples were purchased from Aladdin Biochemical Technology Co., Ltd.
[0054] Method for measuring properties in the examples: Mechanical properties (including tensile strength, elongation at break, modulus) are measured by a universal tensile testing machine.
[0055] Example 1
[0056] This embodiment provides a method for preparing and degrading a degradable resin-based composite material. The specific preparation steps are as follows:
[0057] Take 10 g of zeolite molecular sieve (pore size 5 nm) and soak it in an aqueous solution mixture of 0.5 M sodium sulfate (Na2SO4) and 1 M sodium hydroxide (NaOH), and stir for 2 h. After filtration, dry it at 90 °C for 4 h to obtain porous material 1. Soak porous material 1 in 1,4-butanediol (BDO), and perform ultrasonic-assisted adsorption for 1 h. After filtration, porous material 2 is obtained. Mix 5 g of Fe3O4 magnetic powder (particle size 50 nm) with porous material 2, and 2 ultrasonic for 2 h, and then centrifuge at 5000 rad / min for 10 min to form an aqueous dispersion. Add this dispersion to a 5% PVDF / NMP solution, stir for 1 h, and dry at 100 °C for 1 h after filtration to form porous material 3 (coated with a PVDF nanofilm on the surface). Mix porous material 3 with epoxy resin (EP) at a ratio of 10 wt%, melt-blend at 180 °C for 2 h, and increase the temperature gradient at 40 °C / h. Cure at 120 °C and 0.5 Mpa for 2 h to obtain a degradable composite material. Apply a 250 MHz high-frequency magnetic field (magnetic field strength 5 μT, electric field strength 150 V / m) for 10 min, and the composite material degrades rapidly at a local high temperature (>200 °C).
[0058] It can be seen from Figure 1 that the composite material prepared in this example can be efficiently degraded; it can be seen from Figure 2 that the fiber surface is smooth and free of impurities, indicating that the degradation system can completely degrade the composite material; it can be seen from Figure 3 that the tensile value of a single fiber is 2.93 GPa, indicating that the degradation system will not damage the mechanical properties of the fiber; it can be seen from Figure 4 that there is a strong absorption peak at 3200 cm -1 , indicating that the active degradation resin contains a large amount of hydroxyl and amino groups.
[0059] Example 2
[0060] This example provides a preparation and degradation method of a degradable resin-based composite material. The specific preparation steps are as follows:
[0061] Take 10 g of zeolite molecular sieve (pore size 5 nm) and soak it in an aqueous solution mixture of 0.3 M potassium chloride (KCl) and 0.5 M potassium hydroxide (KOH), and stir for 2 h. After filtration, dry it at 90 °C for 4 h to obtain porous material 1. Soak porous material 1 in N,N-dimethylformamide (DMF), and perform ultrasonic-assisted adsorption for 1 h. After filtration, porous material 2 is obtained. Mix 5 g of Fe magnetic powder (particle size 50 nm) with porous material 2, and 2Ultrasonic treatment for 1 h, then centrifuge at 5000 rad / min for 10 min to form an aqueous dispersion. Add this dispersion to a 5% PVDF solution, stir for 1 h, filter, and dry at 100 °C for 1 h to form porous material 3 (coated with a PVDF nanofilm on the surface). Mix porous material 3 with unsaturated polyester resin at a ratio of 10 wt%, melt-blend at 160 °C for 2 h, increase the temperature gradient at 40 °C / h, and cure at 150 °C and 2 Mpa for 4 h to obtain a degradable composite material. Apply a 200 MHz high-frequency magnetic field (magnetic field strength 3 μT, electric field strength 100 V / m) for 10 min, and the composite material rapidly degrades at a local high temperature (>200 °C).
[0062] Example 3
[0063] This example provides a method for preparing and degrading a degradable resin-based composite material. The specific preparation steps are as follows:
[0064] Take 10 g of MOFs (pore size 5 nm), soak it in an aqueous solution of 0.4 M sodium nitrate (NaNO3) and 0.2 M ethylenediamine, and stir for 2 h. After filtration, dry at 100 °C for 3 h to obtain porous material 1. Soak porous material 1 in dimethyl sulfoxide (DMSO), perform ultrasonic-assisted adsorption for 1 h, and filter to obtain porous material 2. Mix 5 g of Nd2Fe 14 B powder magnetic powder (particle size 50 nm) with porous material 2, and under 0.4 W / cm 2 Ultrasonic treatment for 1.5 h, then centrifuge at 5000 rad / min for 10 min to form an aqueous dispersion. Add this dispersion to a 5% PMMA solution, stir for 1 h, filter, and dry at 100 °C for 1 h to form porous material 3 (coated with a PMMA nanofilm on the surface). Mix porous material 3 with polyurethane (PU) at a ratio of 10 wt%, melt-blend at 200 °C for 1.5 h, increase the temperature gradient at 40 °C / h, and cure at 120 °C and 2 Mpa for 2 h to obtain a degradable composite material. Apply a 200 MHz high-frequency magnetic field (magnetic field strength 8 μT, electric field strength 180 V / m) for 10 min, and the composite material rapidly degrades at a local high temperature (>200 °C).
[0065] Example 4
[0066] This example provides a method for preparing and degrading a degradable resin-based composite material. The specific preparation steps are as follows:
[0067] Take 10 g of montmorillonite (pore size 5 nm) and soak it in an aqueous solution mixture of 0.2 M sodium phosphate (Na3PO4) and 0.1 M ammonia water, and stir for 2 h. After filtration, dry it at 70 °C for 5 h to obtain porous material 1. Soak porous material 1 in benzyl alcohol and perform ultrasonic-assisted adsorption for 1 h, and obtain porous material 2 after filtration. Mix 5 g of FeCo alloy powder magnetic powder (particle size 50 nm) with porous material 2, and 2 ultrasonic for 2 h, then centrifuge at 5000 rad / min for 10 min to form an aqueous dispersion. Add this dispersion to a 5% PS solution, stir for 1 h, filter and dry at 100 °C for 1 h to form porous material 3 (coated with a PS nanofilm on the surface). Mix porous material 3 with epoxy resin at a ratio of 10 wt%, melt-blend at 220 °C for 2 h, and increase the temperature gradient at 40 °C / h. Cure at 150 °C and 6 Mpa for 1 h to obtain a degradable composite material. Apply a 220 MHz high-frequency magnetic field (magnetic field strength 6 μT, electric field strength 120 V / m) for 10 min, and the composite material rapidly degrades at a local high temperature (>200 °C).
[0068] Example 5
[0069] This example provides a method for preparing and degrading a degradable resin-based composite material. The specific preparation steps are as follows:
[0070] Take 10 g of diatomite (pore size 5 nm) and soak it in an aqueous solution mixture of 0.5 M sodium acetate (CH3COONa) and 0.3 M calcium hydroxide (Ca(OH)2), and stir for 2 h. After filtration, dry it at 85 °C for 4 h to obtain porous material 1. Soak porous material 1 in glycerol and perform ultrasonic-assisted adsorption for 1 h, and obtain porous material 2 after filtration. Mix 5 g of SmCo5 powder magnetic powder (particle size 50 nm) with porous material 2, and 2 ultrasonic for 1 h, then centrifuge at 5000 rad / min for 10 min to form an aqueous dispersion. Add this dispersion to a 5% PTFE solution, stir for 1 h, filter and dry at 100 °C for 1 h to form porous material 3 (coated with a PTFE nanofilm on the surface). Mix porous material 3 with polycarbonate (PC) at a ratio of 10 wt%, melt-blend at 240 °C for 1 h, and increase the temperature gradient at 40 °C / h. Cure at 120 °C and 0.5 Mpa for 2 h to obtain a degradable composite material. Apply a 280 MHz high-frequency magnetic field (magnetic field strength 7 μT, electric field strength 160 V / m) for 10 min, and the composite material rapidly degrades at a local high temperature (>200 °C).
[0071] Example 6
[0072] This example provides a method for preparing and degrading a degradable resin-based composite material. The specific preparation steps are as follows:
[0073] Take 10 g of carbon-based porous material (pore size 5 nm) and soak it in an aqueous solution of 0.6 M aluminum sulfate (Al2(SO4)3) and 0.4 M pyridine, and stir for 2 h. After filtration, dry it at 95 °C for 2 h to obtain Porous Material 1. Soak Porous Material 1 in 1,3-propanediol and perform ultrasonic-assisted adsorption for 1 h, and obtain Porous Material 2 after filtration. Mix 5 g of Fe3O4 magnetic powder (particle size 50 nm) with Porous Material 2 and 2 ultrasonic for 1.5 h, then centrifuge at 5000 rad / min for 10 min to form an aqueous dispersion. Add this dispersion to a 5% PE solution, stir for 1 h, and dry at 100 °C for 1 h after filtration to form Porous Material 3 (coated with a PE nanofilm on the surface). Mix Porous Material 3 with polyphenylene sulfide (PPS) at a ratio of 10 wt%, melt-blend at 260 °C for 1 h, and increase the temperature gradient at 40 °C / h. Cure at 150 °C and 10 Mpa for 4 h to obtain a degradable composite material. Apply a 240 MHz high-frequency magnetic field (magnetic field strength 4 μT, electric field strength 140 V / m) for 10 min, and the composite material rapidly degrades at a local high temperature (>200 °C).
Claims
1. A preparation method of a degradable resin-based composite material, characterized in that The method includes the following steps: Step 1: Adsorb an aqueous solution of a metal salt and a strong base in a porous material, dry it, and remove the moisture to obtain a porous material 1 with the metal salt and the strong base adsorbed on its surface, where: the mass ratio of the metal salt to the strong base is 10:90 to 10; Step 2: Immerse the porous material 1 in a degradation solvent, and after adsorption saturation, obtain a porous material 2 adsorbed with the metal salt and the degradation solvent; Step 3: Blend the porous material 2 with a magnetic material, form an aqueous dispersion through ultrasonic treatment and centrifugal purification, then wrap it in a polymer solution to form a polymer nano-sealing film on the surface, filter and dry it to obtain a porous material 3, where: the mass ratio of the porous material 2 to the magnetic material is 100:2 to 60; Step 4: Melt-blend the porous material 3 with a polymer matrix to obtain a degradable resin, and further cure it to obtain a degradable composite material, where: the polymer matrix is one or more of phenolic resin, epoxy resin, unsaturated polyester resin, polyurethane resin, melamine formaldehyde resin, polyether ether ketone, polyphenylene sulfide, polysulfone, acrylonitrile-butadiene-styrene copolymer, polymethyl methacrylate, thermoplastic polyurethane, polyamide, polycarbonate, polyoxymethylene, polyethylene terephthalate, polybutylene terephthalate.
2. The preparation method of the degradable resin-based composite material according to claim 1, characterized in that In the said Step 1, the metal salt is one or more of nitrates, sulfates, chlorides, phosphates, acetates; the strong base is one or more of triethylamine, hexamethylenetetramine, ethylenediamine, propylenediamine, butylenediamine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, pyridine, imidazole, piperidine, sodium amide, sodium sulfide, sodium fluoride, potassium fluoride, ammonia water, sodium hydroxide, potassium hydroxide, calcium hydroxide, barium hydroxide, sodium methoxide, sodium ethoxide, n-butyllithium, methyllithium; the porous material is one or more of porous ceramics, porous metals, porous polymers, carbon-based porous materials, metal-organic frameworks, zeolites, molecular sieves, montmorillonite; in the aqueous solution of the metal salt and the strong base, the mass fractions of the metal salt and the strong base are both 0.5 to 30%; the pore size distribution of the porous material is 2 to 10 nm; the drying temperature is 60 to 120 °C, and the drying time is 0.5 to 24 h.
3. The preparation method of the degradable resin-based composite material according to claim 2, wherein The said nitrate is one or more of sodium nitrate, potassium nitrate, ammonium nitrate, calcium nitrate, lead nitrate, cerium nitrate; the said sulfate is one or more of ferric sulfate, copper sulfate, sodium sulfate, potassium sulfate, potassium alum, sodium sulfate, magnesium sulfate, aluminum sulfate; the said chloride is one or more of sodium chloride, potassium chloride, calcium chloride, magnesium chloride, zinc chloride, ferrous chloride, ferric chloride, copper chloride, silver chloride, barium chloride, ammonium chloride, aluminum chloride; the said phosphate is one or more of ferric phosphate, copper phosphate, sodium phosphate, potassium phosphate, magnesium phosphate; the said acetate is one or more of ferric acetate, copper acetate, sodium acetate, potassium acetate, magnesium acetate.
4. The preparation method of the degradable resin-based composite material according to claim 2, wherein The said porous ceramics are one or more of alumina porous ceramics, silicon carbide porous ceramics, zeolite molecular sieves, diatomite ceramics, zirconia porous ceramics, mullite porous ceramics.
5. The preparation method of the degradable resin-based composite material according to claim 1, wherein In the second step, the degradation solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, benzyl alcohol, phenethyl alcohol, n-hexanol, 1,3-propanediol, glycerol, fructose, pentaerythritol, 1,2-propanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, ethylene glycol, tetramethylbenzyl alcohol, ethyl acetate, isopropanol, and phenethyl alcohol.
6. The preparation method of the degradable resin-based composite material according to claim 1, characterized in that In the third step, the magnetic material is one or two of ferromagnetic materials and ferrimagnetic materials; the polymer solution is one or more of polyvinylidene fluoride solution, polymethyl methacrylate solution, polyethylene solution, polytetrafluoroethylene solution, polyvinyl chloride solution, polystyrene solution, polyacrylate solution, and polypropylene solution; the particle size distribution of the magnetic material is 2 - 10 nm; the mass fraction of the aqueous dispersion is 0.1 - 30%; the intensity of ultrasonic wave is 0.1 - 0.5 W / cm², and the time of ultrasonic wave is 0.1 - 24 h; the intensity of centrifugation is 100 - 10,000 rad / min, and the time of centrifugation is 0.1 - 15 min; the drying temperature is 60 - 150 °C, and the drying time is 0.1 - 2 h.
7. The preparation method of the degradable resin-based composite material according to claim 6, characterized in that The ferromagnetic material is one or more of iron, nickel, cobalt, permalloy, magnetite, neodymium iron boron, samarium cobalt, and alnico.
8. The preparation method of the degradable resin-based composite material according to claim 1, characterized in that In the fourth step, the melting temperature is 5 - 300 °C, the melting time is 0.1 - 6 h, and the gradient heating rate is 10 - 60 °C / h; the curing conditions are a temperature of 20 - 200 °C, a pressure of 0.1 - 20 Mpa, and a curing time of 0.1 - 6 h.
9. A degradable resin-based composite material prepared by the method according to any one of claims 1 - 8.
10. A method for degrading a degradable resin-based composite material prepared by the method according to any one of claims 1-8, characterized in that The method comprises the following steps: The degradable composite material is acted upon by a high-frequency magnetic field, wherein: the frequency range of the high-frequency magnetic field is 20 - 300 MHz, the magnetic field intensity is 0.1 - 10 μT, and the electric field intensity is 1 - 200 V / m.